Training Subjects On Key Concepts From Patient-Reported Outcomes (PROs) Improves Understanding And Data Accuracy [Corrigendum] - Dias, Nadeeka R; Howley, Amanda R; Yamamoto, Rinah; Dallabrida, Susan M (Patient related outcome measures, 2019)
Dias NR, Howley AR, Yamamoto R, et al. Patient RelatOutcome Meas. 2019;10:315-319.Upon reviewing the article, the authors noticed an error inFigure 1 on page 318, it should be presented as follows:The y-axis on the figure previously provided did not accuratelyreflect the values written within the text of the paperas well as the values written above the error bars on thefigure itself. Therefore, the authors have made the correctionsto the y-axis. This change does not alter the findingsreported in the results. The authors apologize for this error.Read the original article